(untitled) (Research, Society and Development, 2022)
The following work addresses the central theme of how nursing works with victims of sexual violence. Objective: to identify how nursing welcomes victims; to investigate the difficulties faced by the nursing team; explain how case notifications should be made; and understand the importance of the bond between nurses and victims of sexual violence. Methods: a research based on literary consultations whose data are on the subject. Being used as a basis for studies in electronic scientific articles, searched in SCIELO databases, virtual health library (VHL), academic articles. Results: sexual violence is one of the most terrible forms of violence that mainly haunts women, with a great impact on sexual and reproductive health. Nursing has a very important role in victim care, and they must have empathy and need to give support, they must be prepared to give proper assistance to victims. It is concluded that, no matter how old sexual violence is, it will always exist in different ways and forms, and it continues to have difficulties on the part of the victim to want to seek help, and on the part of the professional, since most are not prepared to attend.